Reusing biofloc-culture water and microbubble aeration for culturing the white-leg shrimp Litopenaeus vannamei - Ezzah Rahimah Samsuri; Poobalan Ganesan; Iswadi Jauhari; Geok Yuan Annie Tan; Faik A. Hamad (Aquaculture and Fisheries)
This study investigated the effects of reusing biofloc-culture water for culturing the white-leg shrimp Litopenaeus vannamei. Experiments were conducted for two continuous cycles without water exchange for 30 days during the nursery stage. The studies were performed with two different aeration systems, namely microbubbles (MB) and large air bubbles (LB). Water quality parameters such as dissolved oxygen (DO), temperature, pH, salinity, alkalinity, total ammonia nitrogen (TAN), nitrite, nitrate, settleable solids (SS), and total suspended solids (TSS) were recorded throughout the culture days. Also, comparisons were performed on parameters of the shrimp growth, i.e., body weight and length, feed conversion ratio (FCR), and specific growth rates (SGR) for the 30-day culture for Cycles 1 and 2. Cycle 2 showed no deterioration in water quality and no significant difference in growth performance compared to Cycle 1 for either aeration method (MB and LB). However, when comparing between aeration methods, MB aeration significantly improved the DO of the water and accelerated the conversion of TAN to nitrate. Shrimps in the MB aeration system were significantly larger (by 39%) with a lower FCR value (reduced by 30%) than in the LB aeration system. Harmful bacteria from the Vibro group were detected. However, they occurred at a minimum level in both cycles and aeration types. Overall, the biofloc-culture water might be reused for the subsequent cycle, while the MB aeration might promote the growth of biofloc and L. vannamei.